Recurrent epithelial ovarian cancer: an update on treatment - Foley, Olivia W; Rauh-Hain, J Alejandro; del Carmen, Marcela G (Oncology (Williston Park, N.Y.), 2013)
An estimated 85% of patients with epithelial ovarian cancer who achieve a full remission following first-line therapy will develop recurrent disease. Although each subsequent line of therapy is characterized by shorter disease-free intervals, median survival for these patients ranges from 12 months to 24 months. Emerging therapies in the management of ovarian cancer have resulted in a shift in paradigm, including in the appropriate time to institute therapy, and in the selection of therapy. This review focuses on chemotherapy and emerging biologic agents that present a therapeutic option for patients with recurrent ovarian cancer.